Pengaruh Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Minyak, Gas dan Batubara Tahun 2021-2023 - Manik, Triva Maria; Nugraha P, Dios (Magister Ilmu Akuntansi Universitas Jambi, 2024)
The purpose of the study serves to analyze the impact of capital structure and profitability on firm value, with the variable used is firm size as a moderating variable. The sample in this study used 11 industries from oil, gas and coal listed on the Indonesia Stock Exchange. The method of this study uses a quantitative approach, involving descriptive statistics, classical assumption tests, and Moderated Regression Analysis, processing is done with SPSS version 24. The results obtained show that capital structure, which is measured using DER, has no relevant impact on firm value. Profitability, measured by ROA, has a relevant negative impact on firm value. Firm size, measured using total assets, has no relevant impact on firm value. In addition, firm size does not moderate the impact of capital structure and firm value, but moderates the impact of profitability on firm value. Firm size serves as a moderator, which is used in the assessment.